A study of people-centered early warning system in the face of near-field tsunami risk for Indonesian coastal cities. Issue 2 (16th January 2020) - Rahayu, Harkunti Pertiwi; Comfort, Louise K.; Haigh, Richard; Amaratunga, Dilanthi; Khoirunnisa, Devina
Abstract : Purpose: This study aims to identify the gaps in current policy and propose a viable framework for policy improvement regarding people-centered tsunami early warning chain in Padang City. The objectives are: to describe the gaps and flaws in the current policy regarding local tsunami early warning chain, to identify potential actors to be involved in the tsunami early warning chain and to assess the roles and capacity of actors, and their potential for involvement in early warning. Design/methodology/approach: This study is an exploratory study using social network analysis (SNA) on regulations and other legal documents, and primary data sources from a focus group discussion and semi-structured interviews. Findings: The study found that the existed regulation lacks extension nodes to relay warnings to the populations at risk, often referred to as "the last mile." Moreover, receiving warning information from both formal and informal sources is important to mobilize people evacuation more effectively during an emergency. The study found that mosque communities and disaster preparedness leaders are the potential actors who should be involved in the local early warning chain. Practical implications: The research findings were presented as a recommendation to Padang City Government and have been legalized as the new tsunami early warning chain procedure in the Padang City Mayor Regulation 19/2018. Originality/value: This research investigated local tsunami early warning dissemination in Padang City using SNA. The study demonstrates a close collaboration between researchers, practitioners and the community.